2014
DOI: 10.5301/ejo.5000424
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optical Coherence Tomography in Evaluation of Severe Fungal Keratitis Infections Treated by Corneal Crosslinking

Abstract: The different behavior of inflamed tissue with respect to UVA irradiance could be the main point to understand the different postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
0
14
0
4
Order By: Relevance
“…This study not only confirmed the previous results from Seiler and colleagues from the year 2000, but also introduced the concept that CXL might be efficient when treating corneal melts from an infectious origin. Subsequently, further clinical trials on advanced melting corneas, one meta-analysis, and multiple animal experiments confirmed those initial results [ 20 , 26 53 ].…”
Section: Reviewmentioning
confidence: 73%
“…This study not only confirmed the previous results from Seiler and colleagues from the year 2000, but also introduced the concept that CXL might be efficient when treating corneal melts from an infectious origin. Subsequently, further clinical trials on advanced melting corneas, one meta-analysis, and multiple animal experiments confirmed those initial results [ 20 , 26 53 ].…”
Section: Reviewmentioning
confidence: 73%
“…Therapeutisch kann neben den Standardmedikamenten auch das korneale Crosslinking eingesetzt werden [4,5], dies geht aber mit einem erhöhten Risiko der Hornhauteinschmelzung einher. Aufgrund all dieser Probleme ist es deshalb selbst heute nicht sel- ten, dass eine Pilzkeratitis letztendlich zur Enukleation des Auges führt [6,7].…”
Section: Diskussionunclassified
“…Besides being an adjuvant therapy, CXL has been used as a salvage therapy for refractory infectious keratitis in various case reports and series in the literature (Iseli et al 2008;Ehlers et al 2009;Micelli Ferrari et al 2009;Kozobolis et al 2010;Makdoumi et al 2010b;Mor en et al 2010;Anwar et al 2011;Garduno-Vieyra et al 2011;Khan et al 2011;Kymionis et al 2012;Panda et al 2012;Demirci & Ozdamar 2013;Ferrari et al 2013;Li et al 2013;Mattila et al 2013;Rosetta et al 2013;Saglk et al 2013;Sorkhabi et al 2013;Abbouda et al 2014b;Arance-Gil et al 2014;Chan et al 2014;Labiris et al 2014;Shetty et al 2014). Panda et al (2012) applied CXL to seven patients with infectious corneal ulcer who did not respond after 4-12 weeks of topical antimicrobial treatment.…”
Section: Clinical Studiesmentioning
confidence: 99%